Cases in medical microbiology and infectious diseases - Gilligan, Peter H. (ASM Press, 1997)
This text is designed for medical students preparing for the National Board of Medical Examiners exam or those in a clinical rotation. The text presents 68 case histories (15 are new to this edition) with questions to test students on the cases' etiology, diagnosis, pathogenesis, clinical presentation, epidemiology, prevention, and treatment. A lengthy introduction describes various clinical laboratory tests used in diagnosis. New to the third edition is a discussion of cellular microbiology with most of the case studies.